2020
DOI: 10.1634/theoncologist.2020-0518
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Blood Parameters Predict Efficacy from Immunotherapy Agents in Early Phase Clinical Trials

Abstract: Background Peripheral blood parameters are correlated to immune‐checkpoint inhibitor efficacy in solid tumors, such as melanoma and non‐small cell lung cancer. Few data are currently available on the prognostic role of these immune‐inflammatory biomarkers for other solid tumors and immunotherapy combinations. Material and Methods From August 2014 to May 2019, 153 patients with metastatic solid tumors were enrolled in phase I clinical trials testing immunotherapy both as single agents and as combinations. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 59 publications
(89 reference statements)
2
21
1
Order By: Relevance
“…We could confirm the data of many previous studies on CM and other solid cancers that NLR is a potent independent predictor for response to ICI in metastatic CM patients. In line with the present work focusing on the impact of dNLR in stage IV melanoma, Chriscitiello et al [23] recently demonstrated that dNLR may be more accurate in predicting poor outcome than NLR for patients with solid cancers treated with ICI in the context of phase I trials. Moreover, Ferrucci et al [25] reported for the first time similar prospective data for 720 patients under ipilimumab treatment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We could confirm the data of many previous studies on CM and other solid cancers that NLR is a potent independent predictor for response to ICI in metastatic CM patients. In line with the present work focusing on the impact of dNLR in stage IV melanoma, Chriscitiello et al [23] recently demonstrated that dNLR may be more accurate in predicting poor outcome than NLR for patients with solid cancers treated with ICI in the context of phase I trials. Moreover, Ferrucci et al [25] reported for the first time similar prospective data for 720 patients under ipilimumab treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The derived NLR (dNLR), composed of white cell counts (WBC) and absolute neutrophil counts (ANC), has been proposed as a simple alternative to NLR for those studies in which only WBC and ANC have been recorded. Indeed, the absolute lymphocyte count has not been determined in some studies [18][19][20][21][22][23][24][25]. In the present study, we aimed to evaluate the prognostic performance of the dNLR in patients with metastatic CM treated with immune checkpoint inhibitors (ICI).…”
Section: Introductionmentioning
confidence: 97%
“…Elevated LDH and NLR results are associated with poorer survival outcomes in patients treated with immunotherapy in phase I clinical trials, regardless of tumor type [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated high neutrophil to lymphocyte ratio (NLR) as a predictor for poor response to IO. Criscitiello et al [ 115 ] demonstrated that a higher derived neutrophil to lymphocyte ratio was associated with reduced PFS (HR 2.29, p = 0.001) and reduced OS (HR 2.06, p = 0.02). A meta-analysis of 14 retrospective studies with 1225 non-small cell lung cancer patients [ 116 ] further provides evidence for a higher baseline NLR being associated with poor PFS (HR 1.44, p < 0.05) and OS (HR 1.75, p < 0.05), following treatment with nivolumab.…”
Section: Peripheral Blood Cell-based Biomarkersmentioning
confidence: 99%